Time Travel in Kurt Vonnegut’s Slaughterhouse-Five (Patan Pragya, 2021)
This paper deals with Kurt Vonnegut’s experimentation with his notion of time travel in his experimental and postmodern science fiction Slaughterhouse-Five. This paper deals with some statements of problem such as why does the novelist use the idea of time travel? Why does he deconstruct traditional concept of time, traditional plot and history? To show Billy pilgrim’s time travel, the protagonist and war prisoner of Slaughterhouse at Dresden, the linear plot and mechanical/ traditional concept of time is not suitable, so the non-linear plot and the subjective/relative concept of time has been used. Qualitative research methodology has been used. Hence, the theories of Deconstruction, New Historicism and postmodern concept of time have been used. In this context, theorists such as Hengry Bergson, Albert Einstein, Jean-Francois Lyotard and so on and critics/writers such as Lois Tyson, Jago Morrison, Julie Armstrong, Todd F. Davis, OnurIsik, Daisaku Ikeda and so on have been used.